Student Discipline Levels on School Rules and Their Implications in Guidance and Counseling - Mega Hardiana; Afrizal Sano (Jurnal Neo Konseling, 2019)
This research is based on a phenomenon that is still found by students who violate various rules and regulations in schools such as students who are not well-dressed, arrive late to school, absent without information and various other violations. This study aims to describe students' discipline towards school rules in terms of: (1) dressing, (2) timeliness, (3) social behavior, and (4) learning ethics. This type of research is descriptive. The research sample was 177 students at public Senior High School in Tanjung Mutiara, Agam Regency. The research findings revealed that students' discipline on aspects: (1) dressed as very high, (2) on aspects of timeliness classified as high, (3) on aspects of social behavior classified as high, and (4) on aspects of learning ethics classified as high.